2014
DOI: 10.5433/1679-0359.2014v35n2p765
|View full text |Cite
|
Sign up to set email alerts
|

Pre-harvest desiccation with glyphosate and quality of stored soybean seeds

Abstract: Seeds from non-genetically modified soybean cultivars harvested after chemical desiccation of plants with glyphosate may produce abnormal seedlings; these may show phytotoxicity symptoms that could persist even after some time of storage due to accumulation of toxic residues. This study aimed to evaluate the quality of stored soybean seeds harvested after chemical desiccation of plants with glyphosate at R7 stage. Seeds from soybean cultivar 'Conquista' were produced with and without desiccation with glyphosat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Os efeitos negativos nessas variáveis (PN e PNEA) ocorreram após o armazenamento das sementes por seis meses quando houve redução no vigor (Tabela 1). O nível de vigor das sementes afeta o estabelecimento da cultura, o desenvolvimento das plantas, a uniformidade da lavoura e a sua produtividade (Toledo et al, 2014).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Os efeitos negativos nessas variáveis (PN e PNEA) ocorreram após o armazenamento das sementes por seis meses quando houve redução no vigor (Tabela 1). O nível de vigor das sementes afeta o estabelecimento da cultura, o desenvolvimento das plantas, a uniformidade da lavoura e a sua produtividade (Toledo et al, 2014).…”
Section: Resultsunclassified
“…A utilização de dessecantes para antecipação da colheita de sementes tem sido empregada nas culturas, sobretudo na soja (Toledo et al, 2014) e no feijão-comum (Franco et al, 2013) logo após atingirem a maturidade fisiológica buscando facilitar a colheita, diminuir injúrias mecânicas, ataque de pragas e microrganismos após o período de maturidade fisiológica (Toledo et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Desiccants have been used to uniformize maturation and promote early harvest of seeds in various crops, such as soybean (Daltro et al, 2010;Marcandalli et al, 2011;Toledo et al, 2014), canola (Silva et al, 2011) and common beans (Kappes et al, 2012;Franco et al, 2013). However, Daltro et al (2010) observed that glyphosate negatively interfered with germination and initial development of soybean seedlings, particularly hampering their roots due to the phytotoxic effect caused by the desiccant.…”
Section: Resultsmentioning
confidence: 99%
“…Moisture content (A) and germination (B) of crambe (Crambe abyssinica Hoechst) seeds with and without plant desiccation at pre-harvest with glyphosate, at different times of application *Significant at 5% probability level by t-test Ns Not significant at 5% probability level by t-test Times of application (days) different times of glyphosate application, maintaining a mean value of 58%. Toledo et al (2014) observed that the germination of soybean seeds, after accelerated aging, was reduced with the desiccation of the plants at pre-harvest, due to the increase in the percentage of abnormal seedlings. Defining the desiccant application time is indispensable for the efficiency of the product, because applications performed far away from the period of seed physiological maturity or under unfavorable conditions of climate, especially rainy periods, can compromise seed quality (Santos et al, 2005).…”
Section: Resultsmentioning
confidence: 99%